TINJAUAN YURIDIS PERMOHONAN PEMBATALAN PERDAMAIAN PKPU PADA KASUS PT PRAKASA SEMESTA ALAM: Juridical Review Application For The Cancellation Of Peace Agreement Pt Prakasa Semesta Alam Suspension Of Debt Payment Case - Kertopati, Shahnaz Aura Chairunisa; Sanusi, Heru Pringgodani (Faculty of Law, Universitas Trisakti, 2024)
The global health crisis caused by the COVID-19 pandemic has posed challenges for numerous businesses in meeting their debt obligations within the stipulated timelines. Consequently, the implementation of the PKPU facility is utilized as a measure to address this issue, aiming to facilitate a resolution and foster harmony between the Debtor and the Creditors.The formulation of the problem is whether the application of the principle of good faith in the implementation of the peace agreement by the Debtor has been fulfilled in Decision No. 37/Pdt.Sus-Cancellation of Peace/2021/PN Niaga Jkt.Pst and whether Decision No. 37/Pdt.Sus-Permbatalan Perdamaian/2021/PN Niaga Jkt.Pst complies with applicable regulations. The research method uses normative and analytical laws, collects secondary data which is divided into primary and secondary legal materials, and conducts qualitative analysis with deductive reasoning. Whereas the Debtor did not comply with the provisions of the principle of good faith in an objective sense because he did not carry out the payment of the remaining debt as stated in the peace agreement, he had been in arrears for 4 months without any information showing that there was good faith on the part of the Debtor to pay the debt. Verdict No. 37/Pdt.Sus- Permbatalan Perdamaian /2021/PN Niaga Jkt.Pst is not in accordance with the applicable regulations, namely Article 170 of the Bankruptcy and PKPU Law and Article 1338 paragraph (3) of the Civil Code because the Debtor's actions are categorized as negligent in implementing the Settlement Agreement. bad faith and deserving of bankruptcy refers to the principle of good faith.